The Effect of Electronic Word of Mouth on Brand Image and Purchase Intention of Youth Customers in Kathmandu Valley - Shahi, Gajendra; Sah, Puja (Nepalese Journal of Business, 2024)
This study examines the effect of electronic word of mouth on brand image and purchase intention of youth customers in Kathmandu Valley. Brand purchase of customer is the dependable variable. The independent variables are brand image, price, information usefulness, source credibility and purchase intention. The primary source of data is used to assess the opinions of the respondents regarding the electronic word of mouth on brand image and purchase intention of youth customers in Kathmandu Valley. The study is based on primary data of 135 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing brand image and purchase intention of youth customers during in Kathmandu Valley. The study showed that brand image and information usefulness have positive impact on brand purchase of customer. It indicates that increase in brand image and information usefulness leads to increase in brand purchase of customer. Likewise, source credibility has a positive impact on brand purchase of customer. It indicates that increase in source credibility leads to increase in brand purchase of customer. Similarly, purchase intention has a positive impact on brand purchase of customer. It means that increase in purchase intention leads to increase in brand purchase of customer. Moreover, price has a negative impact on brand purchase of customer. It indicates that increase in price leads to decrease in brand purchase of customer.